Difference equations of Volterra type and extension of Lyapunov's method. (1990) - Zouyousefain, M.
Abstract : In this paper, the stability properties of nonlinear difference equations of Volterra type is discussed. For this purpose some comparison Theorems are developed, then using these results the stability of the nonlinear difference equations of Volterra type is investigated.